Intrinsic Interference: a New Type of Viral Interference - Marcus, Philip I. (1967)
The hemadsorption-negative plaque test has revealed a new type of viral interference, termed intrinsic interference. Several unrelated types of noncytopathic viruses were shown to induce in infected host cells a state of interference unique in being directed solely against superinfection by Newcastle disease virus (NDV). The NDV-refractory state arises only in those individual cells of a population actually infected by the inducing virus, and presumably results from the action of a protein(s) coded for by the viral genome. Thus, intrinsic interference differs fundamentally from that mediated by an extrinsic protein detectable under conditions favoring resistance to a broad spectrum of viruses and characteristic of interference induced by interferon, the latter being coded for by the cell genome. Intrinsic interference is defined as a viral genome-induced cellular state of resistance to challenge by high multiplicities of NDV, coexistent with a state of susceptibility to a broad spectrum of other viruses, similarly tested at high multiplicities. The capacity to induce intrinsic interference was demonstrated with rubella virus, Sindbis virus (arbovirus, group A), West Nile virus (arbovirus, group B), poliovirus (MEF, type 2), the lactic dehydrogenase virus (Riley's agent), and an unidentified nonhemadsorbing, noncytopathic adventitious virus. A state of intrinsic interference was also observed in the V5 line of mouse cells carrying a murine leukemia virus, probably resulting from some heretofore unsuspected contaminating virus. The molecular basis for intrinsic interference is not known, but it appears to involve a step in the NDV growth cycle beyond that of viral attachment, entry, and eclipse.